Pengaruh size, profitabilitas dan likuiditas terhadap kebijakan hutang perusahaan BUMN di Indonesia (Jurnal Kajian Manajemen Bisnis, 2022)
This study aims to analyze the effect of size, profitability and liquidity on debt policy. The sample of this study is 16 State-owned listed companies for the 2017-2021 time periods. The sampling method is used purposive sampling techniques, namely by using certain criteria, so that it has a sample of 16 companies. The estimation model of this study used the model panel. The results show that firm SIZE and current ratio have a negative effect and significant on leverage. The different results find that profitability has a positive effect and significant on leverage of State-owned companies. This means that increase the profitability would led to increase the leverage, which means that the company maybe pays dividends and the internal funds are reduced and the company willing to increase external financing. In this case, it can be concluded that the debt policy of State-owned companies continues to increase even though the Return on Asset Increases. The implication of the results of this study is that companies that have a high level of profitability are more interested in using debt, but the consequences of high debt more that optimal level, would be possibility of bankruptcy. This is due to the interest expense paid periodically, despite the advantages of taxes.